2014
DOI: 10.1002/mrm.25565
|View full text |Cite
|
Sign up to set email alerts
|

Highly undersampled contrast-enhanced MRA with iterative reconstruction: Integration in a clinical setting

Abstract: While sparse MRI techniques have not yet reached clinical routine, this study demonstrates the technical feasibility of high-quality sparse CEMRA of the whole head in a clinical setting. Sparse CEMRA has the potential to become a viable alternative where conventional CEMRA is too slow or does not provide sufficient spatial resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…From the accepted imaging data, images are jointly reconstructed by optimizing a cost function of the form: min1(12||Axy||22+||Wx||1) with x being the reconstructed 3D+time image series, y the accepted k ‐space data, and A the system operator consisting of multiplication with coil sensitivities, Fourier transformation, and masking. Finally, W is the redundant Haar wavelet transformation including regularization factors that is applied in the phase‐encoding directions and the time direction …”
Section: Methodsmentioning
confidence: 98%
“…From the accepted imaging data, images are jointly reconstructed by optimizing a cost function of the form: min1(12||Axy||22+||Wx||1) with x being the reconstructed 3D+time image series, y the accepted k ‐space data, and A the system operator consisting of multiplication with coil sensitivities, Fourier transformation, and masking. Finally, W is the redundant Haar wavelet transformation including regularization factors that is applied in the phase‐encoding directions and the time direction …”
Section: Methodsmentioning
confidence: 98%
“…SPARSE with sensitivity-encoding reconstruction was implemented by using a fast iterative soft-thresholding algorithm (22) with a redundant 3D Haar wavelet transform to solve sparsity-based optimization problems with comparatively fast convergence and low computational burden. The algorithm uses soft thresholding in the wavelet space of the image, resulting from the contribution from all coils to enforce sparsity (by keeping the high-value coefficients and excluding the low-value coefficients) followed by coil-by-coil evaluation of data consistency to ensure that the reconstructed image is compatible with the acquired data (Fig 1) (23). This algorithm was implemented in the C++ programming language by using multithread programming and was integrated on a standard clinical imaging reconstruction computer.…”
Section: Methodsmentioning
confidence: 99%
“…42 One report describes the use of CS to achieve several 10-fold accelerations during contrast-enhanced MRA. 22 On the other hand, faster acquisition during TOF remains challenging because the arterial signal on NCE MRA is lower compared with that in contrast-enhanced MRA. Only a few studies have reported the application of CS to intracranial 43,44 and peripheral TOF MRA, 45 and extensive evaluations have not been conducted.…”
Section: Figurementioning
confidence: 99%
“…19 Sparse TOF data were reconstructed using a nonlinear iterative sensitivity encoding-based algorithm with a constraint to enforce sparsity. Specifically, images were reconstructed by solving the following minimization problem with a Modified Fast Iterative ShrinkageThresholding Algorithm [20][21][22] :…”
Section: Acquisition Of Mramentioning
confidence: 99%